Quantitative Measurement of Major Secoiridoid Derivatives in Olive Oil Using qNMR. Proof of the Artificial Formation of Aldehydic Oleuropein and Ligstroside Aglycon Isomers. - Evangelia Karkoula; Angeliki Skantzari; Eleni Melliou; Prokopios Magiatis (J Agric Food Chem, 2014)
A previously developed method for measurement of oleocanthal and oleacein in olive oil by quantitative (1)H NMR was expanded to include the measurement of the monoaldehydic forms of oleuropein and ligstroside aglycons. The method was validated and applied to the study of 340 monovarietal Greek and Californian olive oils from 23 varieties and for a 3-year period. A wide variation concerning the concentrations of all four secoiridoids was recorded. The concentration of each one ranged from nondetectable to 711 mg/kg and the sum of the four major secoiridoids (named as D3) ranged from nondetectable to 1534 mg/kg. Examination of the NMR profile of the olive oil extract before and after contact with normal or reversed stationary chromatography phase proved the artificial formation of the 5S,8S,9S aldehydic forms of oleuropein and ligstroside aglycon isomers during chromatography. Finally, methyl elenolate was identified for the first time as a minor constituent of olive oil.